IMPROVEMENT OF THE MANAGEMENT MECHANISM OF THE STRATEGY OF INNOVATIVE ACTIVITIES OF ENTERPRISES - Череп, Олександр; Череп, Алла; Огренич, Юлія; Гельман, Валентина; Горбунова, Анна (Fìnansovo-kreditna dìâlʹnìstʹ: problemi teorìì̈ ta praktiki (Online), 2024)
The article is concerned with the interpretation of the essence of the innovation strategy concept given the impact of environmental factors in order to meet the interests of all parties concerned, with the author's definition of this concept suggested. The author's typology of innovation strategies, which are characterized by their advantages and disadvantages for the industrial enterprise, is provided. The main elements of different types of innovation strategies are analyzed and characterized. The relation between the classification features and essential characteristics of different types of innovation strategies is established. On the basis of a comprehensive approach to the formation of an innovative activity strategy, the mechanism of managing the innovative activity strategy has been improved with allowances made for the factors of the external and internal environment, as well as the interconnected stages of its implementation. According to the results of the research on the state of innovative activity of industrial enterprises and forecasting of its results, the necessity of using tools to increase the efficiency of the strategy of innovative activity, namely the mechanism of managing the strategy of innovative activity, which will allow to resume the innovative development of enterprises, will contribute to the improvement of financial indicators.